Digital Implant-Supported Restoration Planning Placed in Autologous Graft Using Titanium Implants Produced by Additive Manufacturing - Rafael Seabra Louro; Vittorio Moraschini; Fernando Melhem-Elias; George Patrick Sotero Sturzinger; Renata Augusto Amad; Jamil A. Shibli (MDPI AG, 2024)
This clinical report presents a technique to reconstruct extensively resected mandibles using a combination of autologous bone grafts and additive manufacturing techniques. Mandibular defects, often arising from trauma, tumors, or congenital anomalies, can severely impact both function and aesthetics. Conventional reconstruction methods have their limitations, often resulting in suboptimal outcomes. In these reports, we detail clinical cases where patients with different mandibular defects underwent reconstructive surgery. In each instance, autologous grafts were harvested to ensure the restoration of native bone tissue, while advanced virtual planning techniques were employed for precise graft design and dental implant placement. The patients experienced substantial improvements in masticatory function, speech, and facial aesthetics. Utilizing autologous grafts minimized the risk of rejection and complications associated with foreign materials. The integration of virtual planning precision allowed customized solutions, reducing surgical duration and optimizing implant positioning. These 2 cases underscores the potential of combining autologous grafts with virtual planning precision and dental implants produced by additive manufacturing for mandible reconstruction.